Identification of Physics Concepts in The Songket Tower of South Solok as The Basis for The Design of Physics Edupark Enrichment Books - Putri, Melvia Nisa; Rifai, Hamdi; Fauzi, Ahmad; Yumna, Hayyu (Universitas Negeri Padang, 2025)
A natural or artificial tourist attraction that allows it to be used as part of the learning process in helping educators and students in finding facts, formulating principles or concepts in a physics lesson is called an edupark. Attractions not only offer natural beauty, but also provide a variety of educational information that can support the learning process of students. One of the attractions that can be utilized as an edupark location is the South Solok Songket Tower. This research aims to identify physics concepts in the South Solok Songket Tower as a basis for designing a physics edupark enrichment book. The stage carried out is Edupark Finding, where the process of selecting attractions that meet certain criteria such as, have never been used as research objects, are easily accessible, and have physics concepts. Based on this stage, the South Solok Songket Tower was chosen as the edupark location. The next stage is the Direct Observation stage in the form of direct observation to the location to identify physics concepts contained in the Songket Tower tourist attraction. The observation data was then analyzed as a basis for designing edupark-based physics enrichment books. The results of this observation show that there are many physics concepts contained in the songket tower that can be utilized in learning, so that it can be used as a basis for designing a physics edupark enrichment book .